2020
DOI: 10.1038/s41598-020-58654-8
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Manifestations of Leukemia and Results of Treatment with Intravitreal Methotrexate

Abstract: ocular involvement in leukemia is considered rare. ocular symptoms can be the presenting signs of leukemia, they can appear after diagnosis has been established, or they can be the first manifestation of a relapse after remission. We report, to the best of our knowledge for the first time, the ocular manifestation of a series of patients with ocular leukemia and the result of their treatment with intravitreal methotrexate (MtX) injections. this is a retrospective cohort study. the medical records of 12 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 15 publications
1
27
0
2
Order By: Relevance
“…Intrathecal chemotherapy alone however may yield limited treatment efficacy. Recently, a retrospective cohort study by Vishnevskia et al stated that intravitreal methotrexate injections may be an effective mode of treatment for eyes with intraocular leukaemic tumour cell infiltration whereby in their study 11 treated eyes showed improvement in the inflammatory reaction and tumour cell infiltration and this could be a promising therapeutic approach in future [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal chemotherapy alone however may yield limited treatment efficacy. Recently, a retrospective cohort study by Vishnevskia et al stated that intravitreal methotrexate injections may be an effective mode of treatment for eyes with intraocular leukaemic tumour cell infiltration whereby in their study 11 treated eyes showed improvement in the inflammatory reaction and tumour cell infiltration and this could be a promising therapeutic approach in future [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…2008; Vishnevskia‐Dai et al. 2020). Intravitreal chemotherapy, such as MTX, has shown satisfactory results in cases with diffuse retinal or optic nerve leukaemic infiltration.…”
Section: Figmentioning
confidence: 99%
“…Leukaemic retinopathy is a common ophthalmic presentation of ocular leukaemia; (Talcott et al 2016), and it may occur at the time of primary diagnosis, but it has also been described as a form of leukaemic relapse (Lyu et al 2018). Treatment options are mainly based on chemotherapy, administered either systemically or intravitreally (Frenkel et al 2008;Vishnevskia-Dai et al 2020). Intravitreal chemotherapy, such as MTX, has shown satisfactory results in cases with diffuse retinal or optic nerve leukaemic infiltration.…”
mentioning
confidence: 99%
“…They can be the first manifestation of leukemia (either primary or secondary), occur after the diagnosis has been established, or be the first sign of a relapse after remission [ 2 ]. Secondary ocular manifestations include retinal hemorrhages and retinal venous occlusions due to hematologic abnormalities [ 2 ]. Primary ocular leukemic infiltration can also affect the orbit, anterior segment, and the uvea.…”
Section: Introductionmentioning
confidence: 99%